The impact of pre-drying and different infrared powers on some quality parameters of apple chips fried by vacuum-combined infrared radiation - S. Uğurlu; T. Yücel; İ. Cavidoğlu; E. Bakkalbaşı (Grasas y Aceites)
In this study, the use of vacuum-combined infrared radiation (VCIR) as a frying technique for the production of apple chips was investigated. The effects of a pre-drying treatment before frying on the quality parameters of apple chips were also evaluated. While the frying time of apple slices decreased by increasing the infrared power, the browning index value, 5-hydroxymethylfurfural (HMF) content, and oxidation ratio were raised. The frying times, oil contents, browning, and oxidation rates of apple chips were decreased with the pre-drying treatment. The sensory analyzes showed that the samples fried by vacuum-combined infrared radiation had the highest scores in all sensory characteristics than deep-fat fried samples. Pre-dried apple samples (41% moisture) fried at 350W infrared power under 400 mmHg vacuum pressure had the highest score for general acceptance. The results showed that VCIR would be an alternative frying method for producing healthier apple chips with less oil content and higher quality.